2016
DOI: 10.1007/s00484-016-1210-3
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of global warming on phenology of spring leaf unfolding remain stable in the long run

Abstract: The impact of spring temperature forcing on the timing of leaf unfolding of plants (temperature sensitivity, S) is one important indicator of how and to what degree plant species track climate change. Fu et al. (Nature 526:104-107, 2015) found that S has significantly decreased from the 1980-1994 to the 1999-2013 period for seven mid-latitude tree species in Europe. However, long-term changes in S over the past 60 years are still not clear. Here, using in situ observations of leaf unfolding for seven dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 18 publications
5
36
0
Order By: Relevance
“…We are very happy to see that the article from Wang et al (2016) confirmed these finding using a 15-year window, despite using only 927 species-sites combinations, which is about one sixth of the species-sites (5472) used in our study. However, we can not agree with the highlighted conclusion that the significant decrease in ST using 15-year window is not sustained when examining longer term phenological responses to climate warming.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…We are very happy to see that the article from Wang et al (2016) confirmed these finding using a 15-year window, despite using only 927 species-sites combinations, which is about one sixth of the species-sites (5472) used in our study. However, we can not agree with the highlighted conclusion that the significant decrease in ST using 15-year window is not sustained when examining longer term phenological responses to climate warming.…”
supporting
confidence: 53%
“…1980Fu et al ( -1994Fu et al ( and 1999Fu et al ( -2013. The red line shows the ST in Wang et al (2016) over the period 1980-2013. …”
mentioning
confidence: 99%
“…In this study, we only analyzed four potential factors impacting the estimate of S T . However, other influencing factors of S T also existed, including changes in tree age, nonlinear responses of plant development to temperature, and microclimate (Menzel et al, ; Vitasse, ; H. Wang, Rutishauser, et al, ). In the future, if we could manipulate environmental factors separately through experiments, the relative importance of individual factor or the interaction effect of several factors on the S T of plant phenology could be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The S T of leaf phenology of seven European species declined from a cold period (1980–1994) to a warm period (1999–2013), partly due to the reduced chilling (Fu et al, ). However, when comparing the difference in S T between 1951–1980 and 1984–2013 period, the S T of leaf phenology remained stable (H. Wang, Rutishauser, et al, ). The warming experiment using saplings of three woody plants showed that S T of leaf‐out increased at low and moderate warming (Fu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In temperate regions, these phenophases are very sensitive to small changes in temperature [11][12][13]. The advancement in flowering dates is estimated as 1 to 12 days for each 1 • C increase in spring temperature [14][15][16]. Recent studies demonstrated that the flowering date of main woody plants in temperate regions shifted towards earlier by a rate of 2.0 to 9.6 days decade −1 over the last few decades across Europe [17,18], East Asia [19,20], and North America [21,22].…”
Section: Introductionmentioning
confidence: 99%